STRATIFIKASI SOSIAL MASYARAKAT PEMBUDIDAYA IKAN DAN STRATEGI PEMBANGUNAN BUDIDAYA PERIKANAN DI KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - Hardin, Aisna; Fitriyana (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
Abstract The objectives of this study were to identify the social strata/layers of the fish farming community in Samarinda City and to determine the strategy for aquaculture development in Samarinda City. Respondents in this study were selected using purposive sampling with a total of 26 respondents from fish farmers and 5 staff of the Fisheries Service. Data were analyzed using descriptive qualitative and quantitative and SWOT analysis. The results of the study found that there are two social stratifications in the cultivation community in Samarinda City, namely middlemen/collecting traders and owner fish farmers. Positions as middlemen/collecting traders and fish farmers are status roles that are obtained because they are fought for through their own choices or efforts (achieved status). The top social layer is occupied by middlemen or collecting traders by looking at the level of wealth owned (ownership of vehicles, living conditions and ownership of luxury goods). The strategy that can be carried out for the development of aquaculture in Samarinda City is an aggressive strategy, namely optimizing technology and infrastructure to support the marketing of aquaculture products.